EVALUASI SISTEM INFORMASI REGISTRASI (SIREG) SELEKSI PENERIMAAN MAHASISWA BARU (SIPENMARU) POLITEKNIK KESEHATAN KEMENKES SURAKARTA MENGGUNAKAN FRAMEWORK COBIT 2019 - kantona, riki kantona; fitriasih, sri hariyati; raharja, bayu dwi (STMIK Sinar Nusantara, 2024)
Health Polytechnic of the Ministry of Health Surakarta uses the Registration Information System (SIREG) as a tool for New Student Admission Selection (SIPENMARU) processing registration data in order to improve efficiency, performance and provide valid information . In implementing the Registration Information System, In the use of SIREG to date, no audit or evaluation of the implementation of the system has ever been carried out. Given the importance of the function of SIREG on performance performance in new student admission services, it is necessary to conduct an evaluation related to the assessment of the maturity level of the implementation of the SIREG application, with this evaluation it can determine the extent of the implementation of IT governance, especially in the Registration Information System. From this, the purpose of this study is to evaluate the maturity level of the Registration Information System. This research uses reference to the COBIT 2019 Framework framework domain, namely APO (Align, Plan and Organize): APO-04 and APO-12. The results of the maturity level research in the objective domain APO04 (Innovation Management) get a value of 3.3 with Level 3 Category: Defined and there is a gap of 1.7 so that agencies still need to prepare documentation related to the evaluation and follow-up of innovations in IT governance development, especially in the Registration Information System to achieve a maturity level achievement index of 4 (Quantitative), the objective domain APO12 (Risk Management) gets a value of 1.89 with Level 2 Category: Manage, and there is a gap of 3.11 so that agencies still need to prepare documentation related to planning, monitoring, evaluation and follow-up of IT governance risk management, especially in the Registration Information System to achieve a maturity level achievement index of 3 (Defined).